Clinical profile of patients with obstructive jaundice: a surgeon’s perspectives - Khan, Zubair Afzal (International Surgery Journal, 2019)
Background: There are various causes of obstructive jaundice, choledocholithiasis– the commonest. Patients with obstructive jaundice usually present with complain of yellow skin and eyes, pale stools, dark coloured urine, jaundice, and pruritus.Abdominal pain often misleading for diagnosis. The objectives of the study were to study the clinical profile of patients with obstructive jaundice. Methods: The study included the patients clinically diagnosed as suffering from obstructive jaundice. Thorough history taking and clinical examination was done. Patients undergone for various laboratory investigations, and radiological evaluation. Results: A total 201 patients were included in the present study. Males are more affected (55.72%) as compared to females. Elder age groups (>65 years; and 55-65 years) were commonly affected. 58.71% of patients have malignant causes for development of obstructive jaundice as compared to benign causes in 41.29% of patients. Choledocholithiasis (30.35%) is the commonest cause of obstructive jaundice followed by carcinoma of pancreas (25.87%). Jaundice is the commonest symptom of presentation. Conclusions: Better understanding of the clinical profile in the patients with obstructive jaundice will facilitate appropriate management and lead to improved survival.